Beyond the binary: a rational choice analysis of women's agency in marriages with transgender women in Indonesia - Rina Minita Gusliana; Delmira Syafrini; Fatmariza Fatmariza; Wirdanengsih Wirdanengsih (Jurnal Konseling dan Pendidikan, 2026)
Research on non-normative family forms has largely focused on same-sex relationships or transgender individuals’ personal identities, while little attention has been given to marriages between transgender women and women in socially conservative settings. This study examines women’s motives for marrying transgender women, the strategies couples use to sustain their households, and community responses to these unions in Kaur Regency, Indonesia. The research employs an interpretive phenomenological approach to explore how women interpret and rationalize their marital decisions within a context characterized by strong marital expectations, limited relational options, and persistent social stigma. Data were collected through in-depth interviews, non-participant observation, and document analysis involving seven transgender women–women couples and several supporting informants. The findings reveal that women’s marital decisions were shaped by reflective evaluations of relational safety, emotional stability, and prior experiences in heterosexual relationships. Household sustainability was maintained through adaptive practices such as open communication, negotiated economic responsibilities, and flexible gender roles. Community reactions were characterized by ambivalence, combining normative stigma with pragmatic tolerance when couples were perceived as maintaining social harmony. These findings extend rational choice perspectives by demonstrating how emotional security and relational stability function as central criteria in marital decision-making under socially constrained conditions.